Babe : the gallant pig - King-Smith, Dick.; Rayner, Mary (New York : Bullseye Books, 1995)
A piglet destined for eventual butchering arrives at the farmyard, is adopted by an old sheep dog, and discovers a special secret to success.
Originally published in Great Britain under the title: The sheep-pig.
Elem. School Library Collection
Notable/Best Books (A.L.A.)
Wilson's Children
5.8
3-6.
Keywords: Domestic animals -- Fiction; Pigs -- Fiction; Domestic animals -- Fiction; Pigs -- Fiction